Effect of techniques, trays and materials on accuracy of impressions clinically made - Aion Mangino MESSIAS; Stephania Caroline Rodolfo SILVA; Filipe de Oliveira ABI-RACHED; Raphael Freitas SOUZA; José Maurício dos Santos Nunes REIS (Universidade Estadual Paulista, 2019)
Abstract Introduction Making accurate and dimensionally stable impressions to duplicate oral conditions and tooth morphology is an essential step of prosthetic dentistry for fabricating well-fitted indirect restorations and, consequently, ensure the longevity and success of the treatment. Several authors describe pros and cons of different impression techniques, although there is no unanimity among them about the best one. Objective This study evaluated casts' accuracy made by different impression techniques, trays and materials. Material and method 10 patients were selected and 20 impressions from teeth #13 to #16 were performed using single-step (SS) and two-step techniques, made with metal stock and customized acrylic resin partial trays, vinyl polysiloxane and condensation silicone rubbers. Type IV gypsum was used to pour the casts. Three photographs of each patient (baseline), as their respective gypsum casts, were taken, measured in their interested buccal surface area. Comparisons of area values among experimental groups and baseline were performed. Data showed adherence to normal curve, being submitted to 3-way ANOVA/Bonferroni test (α=.05). Result Technique produced significant differences (P=0.02). SS technique was more accurate than BUR one (P=0.003; 95=1.22 to 5.98), but both resulted in similar casts to PVC, MOV and NR techniques, which were similar to each other (P>0.05). Conclusion SS technique showed the closest absolute values to baseline.